Idiopathic spinal cord herniation syndrome: a case report - Manda, Venkata Vijaya Sekhar; Kuppili, Venkata Ramprasad; Vasupalli, Ravi; Devaguptapu, Surya Ganapathi Rao (International Journal of Research in Medical Sciences, 2017)
Idiopathic spinal cord herniation syndrome is a rare entity. Only 17 cases have been reported in literature so far. They typically occur in the dorsal region of the spinal cord, spontaneously, through a defect/rent in the anterior Dura. Majority present in middle age women, with progressive paraparesis/asymmetrical motor weakness in lower limbs.